Tobacco, alcohol, illegal drug and substance use, sociodemographic variables and psychological distress symptoms in individuals aged 50-65 (Annals of Medical Research, 2024)
Aim: The aim of the study is to evaluate the relationship between tobacco, alcohol, illegal drug and substance use, demographic variables and symptoms of psychological distress in individuals aged 50-65 living in the city center of Erzrurum, and to create a risk profile based on these variables.Materials and Methods: The data of the study were collected through survey forms. Participants filled out the sociodemographic-clinical data form, Fagerström Nicotine Dependency Test (FNDT), Symptom Checklist 90-Revised (SCL90-R).Results: Three hundred twelve participants, 154 women and 158 men, were included in the study. 43.3% of the participants were smoking, 10.3% were using alcohol, and 3.8% were using illegal drugs and substances. The SCL90-R subscale scores and overall symptom severity were significantly higher in smokers and alcohol users compared to non-users, except for somatization. Moderate significant positive correlations were found between the FNDT scale score and the SCL90-R scale scores. It was found that male gender increased tobacco use by approximately 10.7 times (OR:10.7, 95%  CI [5.721, 20.113]), a one-unit increase in paranoia increased it by 3.4 times (OR:3.4, 95% CI [2.373, 4.963]), while a one-unit increase in age decreased it by 0.9 times (OR:0.9, 95% CI [0.900, 0.976]).Conclusion: It has been observed that tobacco and alcohol use in early old age is closely related to symptoms of psychological distress.It can be said that preventive interventions for the psychological health of the community may be important in combating tobacco and alcohol use.
Keywords: Tobacco use; Alcohol use; Substance use; Symptoms of psychological distress; Early old age